Analisis Kesulitan Siswa Dalam Menyelesaikan Soal-soal Segitiga Setelah Pembelajaran Kooperatif : (Studi Kasus Siswa SMP Tamansiswa Diski) - Meman Marpaung (Cendikia : Media Jurnal Ilmiah Pendidikan, 2021)
The problem in this study is: How to describe the difficulty of students working on triangular problems after the provision of cooperative learning. The goal to be achieved in this study is: getting an overview of the difficulty of students working on triangular problems after the provision of cooperative learning to tamansiswa Diski junior high school students. The population in this study is a student of class VII Tamansiswa Diski Junior High School who is actively enrolled which numbers 148 people. The determination of the sample of authors was done in a random way as many as 30 people taken from class VII students. The data collection tool used in this study is: The test that provides mathematical problems about the triangle as much as 10 points of the test form problem is an "essay test". Before this test is established as an instrument in the data collection in this study, it is first piloted to non-sample, to find out the validation of the test, the reliability of differentiating power and the difficulty level of the test. From the results of the discussion, the research conclusion was obtained that after the provision of cooperative learning the difficulties of students working on triangular problems can be overcome. The difficulties experienced by tamansiswa diski junior high school students are students: less able to distinguish the shapes of triangles, unable to use formulas, do not know the formula to find the circumference of the triangle, and do not use arcs.